2004
DOI: 10.1359/jbmr.0301246
|View full text |Cite
|
Sign up to set email alerts
|

BMD Is Reduced in HIV-Infected Men Irrespective of Treatment

Abstract: Osteoporosis has be reported to be a complication of active antiretroviral therapy of HIV infection. We studied 148 HIV-infected men stratified according to their treatment. Our data show that these patients have an average 9% decreased BMD, irrespective of their treatment. Low body mass index and high resorption markers were associated with low bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 33 publications
3
89
4
Order By: Relevance
“…Available data on the role for HIV-related factors in bone loss among HIV-1-infected patients are conflicting [6]. Some studies have suggested that the use of protease inhibitor and of TDF was associated with an increased risk of osteopenia and osteoporosis [1,12,17,24,25] while others failed to confirm this association [18,20,26,27]. In the present study, neither protease inhibitors nor TDF was associated to bone loss with statistical significance, although weak trends of association were observed at several sites for TDF.…”
Section: Discussioncontrasting
confidence: 70%
“…Available data on the role for HIV-related factors in bone loss among HIV-1-infected patients are conflicting [6]. Some studies have suggested that the use of protease inhibitor and of TDF was associated with an increased risk of osteopenia and osteoporosis [1,12,17,24,25] while others failed to confirm this association [18,20,26,27]. In the present study, neither protease inhibitors nor TDF was associated to bone loss with statistical significance, although weak trends of association were observed at several sites for TDF.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, antiretroviral treatment and mainly protease inhibitors are associated with reduced BMD, although the results of different studies are controversial [26,30,31]. Recently, the long-term adverse events from highly active antiretroviral therapy administration, especially lipid and glucose metabolism disorders, are studied, but the results are not consistent as well [32][33][34]. In our study, the exact mechanism for the more severe bone loss observed in the HIV-positive patients could not be explained by the measurement of bone markers, as we found no significant differences between HIV-positive and HIV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Low body weight has been cited as a causative factor for low BMD in HIV patients. [105][106][107] Conversely, central obesity, as a result of lipodystrophy and associated lipid abnormalities, could play a role in the development of low BMD in HIV-positive patients receiving HAART. A study in HIV-positive men with lipodystrophy demonstrated significant associations between postprandial hyperglycemia and low BMD.…”
Section: Discussionmentioning
confidence: 99%
“…[101][102][103][104][105][106][107][108] Protease inhibitors have been suggested as causative agents for a low BMD, 109 although other studies have not been able to support this fi nding. 101,[103][104][105][106][107][108]110 A meta-analysis of osteoporosis in HIVpositive patients examining data from 20 cross-sectional studies showed a 15% increased prevalence of osteoporosis among HIV-positive subjects compared to HIV-negative controls. Compared to HAART-naïve HIV-positive subjects, receptor and peroxisome proliferator-activated receptor type-γ (RXR-PPARγ) heterodimer, potentially promoting reduced differentiation and increased apoptosis of peripheral adipocytes.…”
Section: Lipid and Bone Metabolism In Hiv/haartmentioning
confidence: 99%